Impact of an educational demand-and-supply policy on girls' education in West Africa: Heterogeneity in income, school environment and ethnicity - Mafaïzath A. Fatoke-Dato (Bamberg University, Bamberg Economic Research Group (BERG), 2015)
The present paper measures the impact of an educational demand-and-supply side policy in a developing country, Benin. This West African country has introduced in 2006 a program to eliminate school fees, build schools and recruit teachers. The data used are the National Demographic and Health Surveys of 2006 and 2012. The difference-in-differences estimations reveal that the policy has lead to a huge increase in enrollment and attendance of birth cohorts of children eligible for the program. Indeed, children stayed on average two more years in school following the implementation of the program. Nevertheless, the gender disparities are tenacious. The heterogeneity analyses suggest that girls' schooling is also influenced by the school infrastructure and the cultural beliefs.
Keywords: H43; I24; I25; I28; 330; Policy evaluation; Education policy; School fees; Inequality; Infrastructures